Deliberating Just War. Issue 1 (March 2015) - Norris, Kristopher
Abstract This essay responds to James Turner Johnson's critiques of my argument in "'Never Again War': Recent Shifts in the Roman Catholic Just War Tradition and the Question of 'Functional Pacifism.'" (2014). It attends specifically to three of Johnson's objections and offers accounts of the meaning and use of the term "functional pacifism, " an understanding of classic just war thought as a tradition, and the concepts of peace and authority within just war and pacifist thought. It argues that my analysis of the Catholic Church's movement toward pacifism but ultimate theological inability to embrace a functional pacifism still stands in spite of Johnson's critiques. In addition, it suggests that Johnson offers a thin pacifistic conception of peace and promotes a restricted notion of ecclesial authority and democratic government.